Implementation of Savings and Loans Business in Village-Owned Enterprises (Bumdes) Based on Government Regulation Number 11 of 2021 Concerning Village-Owned Enterprises - Iwan Pane; Muhammad Yusuf Siregar; Wahyu Simon Tampubolon (Journal of Social Research, 2022)
Background: The seriousness of the Government in building social welfare is evidenced by the creation of Law Number 6 of 2014 concerning Villages. In the mandate of Law Number 6 of 2014 regarding Villages, the Government has created a program to alleviate poverty. Namely, the establishment of Village-Owned Enterprises (BUMDes) is a village-owned enterprise established by the village government whose capital, the village government, and the community carry out ownership and management. The existence of BUMDes is expected to move the wheels of the economy in the village. Objective: This research belongs to the normative type of research. So it can be known that the implementation of credit agreements with Village-Owned Enterprises (Bumdes) in Indonesia allows economic turnover in villages where there are Village-Owned Enterprises. Method: This research belongs to the normative type of research. So it can be known that the implementation of credit agreements with Village-Owned Enterprises (Bumdes) in Indonesia allows economic turnover in villages where there are Village-Owned Enterprises. Result: It can be said that the creditor in the credit relationship with the debtor within the time and conditions mutually agreed upon can return or repay the credit in question. Conclusion: Based on the results of research and discussion, the implementation of credit agreements with Village-Owned Enterprises (Bumdes) in general in Indonesia, it is allowed for an increase in economic turnover in villages where there are Village-Owned Enterprises.